Rudolph Erzherzog von Oesterreich - Wolf, Franz, 1795-1859 (artist):::Creator::::::::::::; Kunike, Adolph Friedrich, 1777-1838 (lithographer):::Contributor:::::::::::: (Austria; Vienna)
Portrait of Archduke Rudolph printed by Adolph Friedrich Kunike based on the work by Franz Wolf.